Strategy to Improve Employees Performance by Implementing a Paternalistic Leadership Style and Enhancing Intrinsic Motivation - Rizaldi, Arjuna (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to analyze the impact of paternalistic leadership style and intrinsic motivation on the improvement of employee’s performance. The research was conducted on agriculture company with the employees as the research subject. The data used in this research were both primary in form of questionnaire as well as secondary data obtained from various scientific literature such as academic journals, textbooks, and various documents from the company. The Multiple Linear Regression was used to analyze the respondent’s answer, and the hypotheses were tested using the t-test and f-test. The result shows that the employee’s performance was significantly affected by paternalistic leadership style and intrinsic motivation of the employee, both partially and simultaneously. Which means that employee’s performance will improve by implementing paternalistic leadership style and enhancing intrinsic motivation of the employee. This research is expected to have impact on the improvement of employee’s performance by implementing a paternalistic leadership style in order to enhance the intrinsic motivation of the employee.